Lectotypification and a new synonym of Neothorelia laotica (Resedaceae) - Shen, Jian-Yong (Phytotaxa, 2023)
The genus Neothorelia Gagnep. (1908a: 269) is represented by only one species Neothorelia laotica (1908a: 269). The type specimens were collected from Luang Prabang in Laos, and later several specimens were collected from Chiang Mai in northern Thailand. No specimens have been recorded from other countries.